2013
DOI: 10.3109/02699052.2013.794963
|View full text |Cite
|
Sign up to set email alerts
|

Detection of brain amyloid β deposition in patients with neuropsychological impairment after traumatic brain injury: PET evaluation using Pittsburgh Compound-B

Abstract: The absence of Aβ deposition in many patients with chronic neuropsychological impairment after TBI does not support the premise that Aβ pathology progresses over time in the traumatized brain. Early and sequential (11)C-PIB PET examination may clarify the time course of Aβ deposition in the traumatized brain and the relationship between traumatic brain insult and subsequent neuropsychological impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 25 publications
4
42
0
Order By: Relevance
“…[55][56][57][58][59] Alpha-synuclein is significantly increased in TBI patient cerebrospinal fluid. 60 Deposition of aberrant proteins is seen in TBI animal models and patients.…”
Section: Fig 2 Electron Micrographs Of Neocortical Neurons After Trmentioning
confidence: 99%
See 1 more Smart Citation
“…[55][56][57][58][59] Alpha-synuclein is significantly increased in TBI patient cerebrospinal fluid. 60 Deposition of aberrant proteins is seen in TBI animal models and patients.…”
Section: Fig 2 Electron Micrographs Of Neocortical Neurons After Trmentioning
confidence: 99%
“…60 Deposition of aberrant proteins is seen in TBI animal models and patients. 55,57 CMA is a major cellular system for removal of a-synuclein, Tau, huntingtin, ubiquitin carboxyl-terminal esterase L1, calcineurin 1, and the cytoplasmic tail of amyloid precursor protein. 58,61 Many of these neurodegenerative disease-related proteins can act as CMA inhibitors and thus compromise CMA.…”
Section: Fig 2 Electron Micrographs Of Neocortical Neurons After Trmentioning
confidence: 99%
“…235 Another study reported [ 11 C] PiB binding in three of 12 patients with neuropsychological impairment studied 5 to 129 months after injury. 236 Further studies will be required to determine the prevalence and time sequence of b-amyloid deposition in TBI, and its relation to degree of initial injury and subsequent impairment.…”
Section: Chronic Tbimentioning
confidence: 99%
“…There have been significant recent advances in detecting and monitoring axonal injury and Aβ deposition in living TBI patients, using imaging techniques typically applied in clinical studies of aging, MCI, and AD: MRI of axonal injury and connectivity (diffuse tensor imaging (DTI) and high definition fiber tractography) (MacDonald et al, 2007, 2011; Presson et al, 2015) as well as amyloid PET (Eisenmenger et al, 2016; Gatson et al, 2016; Hong et al, 2014; Kawai et al, 2013; Mitsis et al, 2014; Scott et al, 2016). Several of these clinical analyses replicate data from histopathology studies.…”
Section: Role Of Aβ and Aging In Primary And Secondary Effects Of mentioning
confidence: 99%